Visible-Light-Promoted Synthesis of Fusesd Imidazoheterocycle by Eosin Y under Metal-Free and Solvent-Free Conditions - Singh H.K.; Kamal A.; Kumari S.; Maury S.K.; Kushwaha A.K.; Srivastava V.; Singh S. (My University, 2025)
A mild, efficient, solvent free, metal free and operationally simple visible light promoted multicomponent reaction of styrene, 2-aminopyrimidine, and t-butyl isocyanide have been been gathered to provide a variety of fusesd fused imidazoheterocycle using Eosin Y as a photocatalyst. This approach delivers good to excellent yields of imidazoheterocycle using readily accessible and economical starting materials under ambient conditions. The reaction provides a broad substrate scope and is compatible with several functional groups. © 2021 Wiley-VCH GmbH.